Student Motivation: Barriers and Incentives for Agency - Dobryakova, Maria S.; Yurchenko, Olesya V. (Voprosy obrazovaniâ, 2024)
Our starting point was the often-overlooked understanding that motivation problems aren't a diagnosis but a symptom. They indicate the actual issue - an environment insufficient for fulfilling autonomy needs, which often escapes the attention of teachers, parents, and even researchers. Our goal was to develop a framework for exploring the main characteristics of a schoolchild's educational environment to identify the source of motivation problems. To do this, we combined aspects of the self-determination theory of E. Deci and R. Ryan with B. Bernstein's framing theory. The self-determination theory helps to consider human motivation from a psychological point of view, while B. Bernstein's framing theory opens a sociological perspective. Including Bernstein's ideas enriches the motivation analysis, highlighting sociological aspects that are not fully accounted for in the self-determination theory. The result is more comprehensive and, at the same time, more "visible" and easier to operationalize in the context of formal school or home education.